Neighborhood effects of civil conflict. (1990 -2012) - Torres G, Edwin Esteban; Giraldo G, Sebastian; Moncada, Jhonny (Perfil de Coyuntura Económica, 2014)
There have been many papers which have studied the causes of conflict, taking into account causes like natural resources, ethnicity, political problems, and commitment problems, among others. This paper focus on the Law of Universal Gravity of Newton (1687) for trying to see if there could be a neighboring country effect on the probability of a conflict or civil war onset and continuity in a given country, and the effect of the size of the border, and find significant evidence about the distance between countries in the probability of onset a conflict. This may suggest that peaceful countries must be very careful with the relationships with neighbors that are having an armed conflict.